Assessing the effectiveness of national park’s policies and laws in promoting biodiversity conservation and ecological development in Pakistan - Javeed, Banafsha; Huang, Delin; Shangguan, Donghui; Ahsan Mukhtar, Muhammad; Sajjad, Wasim; Banerjee, Abhishek; Yang, Qin; Butt, Asim Qayyum (Frontiers in Environmental Science, 2024)
Ecological history is crucial in ecosystem restoration, serving as a tool to identify and characterize suitable restoration targets. Pakistan has implemented laws and policies to enhance forest sustainability and preserve biodiversity, as it is becoming a global strategy for future water planning and management. This study seeks to analyze the impact of national park policies and laws on various factors, including biodiversity conservation, ecological processes preservation, water resource protection, consumptive and non-consumptive benefits, research and education, and the promotion of recreation and tourism. To assess the effectiveness of established policies in 19 National Parks in Pakistan, a mixed-mode research design was utilized, combining both quantitative and qualitative approaches. Data was collected from 300 participants through a closeended questionnaire employing a Likert scale. Analysis of the collected data was conducted using the software Smart Partial Least Squares (SPLS) method. The findings demonstrate that the existing policies and laws have contributed to the preservation of forest sustainability in Pakistan.The policies related to rRecreation and tourism; cConsumptive benefits; and rResearch are more effective respectively compared to other sets of regulations. The laws and policies related to preservation of ecological processes are least effective. The study suggests that laws related to national parks need to be revised to preserve biodiversity and ecological processes. The preservation of water resources should be a major concern, and the consumptive benefits of these parks should be rechecked. Awareness campaigns are to be part of the expansionary policy framework, and while tourism opportunities should be created, a check on natural resource misuse should be implemented. The non-consumptive benefits of these parks should also be assessed. Due to its potential limitations, such as limited stakeholder analysis, difficulty in creating legitimacy in national parks due to bureaucratic structures, lack of community sensitization, and long-term trends in sustainable conservation strategies, there are certain future research directions that can address challenges in studying the impact of policies on national park habitats. There is a pressing demand for a more dynamic approach to ecological policymaking. Continuous evaluation and adaptation of policies will be essential in creating an environment conducive to sustainable development.